2019
DOI: 10.1111/bph.14672
|View full text |Cite
|
Sign up to set email alerts
|

The potential of memory enhancement through modulation of perineuronal nets

Abstract: With an increasingly aging global population, the incidence of neurological diseases such as dementia is set to increase to unmanageable levels, yet there are currently only symptomatic therapies available for treatment. The mechanisms underlying the development of some forms of dementia, such as Alzheimer's disease (AD), are not yet completely elucidated with several competing hypotheses existing. During the closure of the critical period in the brain, significant compositional changes occur to the neural ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 90 publications
(147 reference statements)
0
32
0
Order By: Relevance
“…We also found that ch'ase induced a decrease in the density of VGLUT1+ terminals in the DLH and adjacent areas of the IntA. The observed differential effects of ch'ase on distinct types of cerebellar synapses might be due to a specific distribution of receptors for CSPGs (69) and/or for Sema3A (19). Purkinje cells show a strong expression of receptors for CSPG-chondroitin sulfates, such as PTPsigma and NgR3 (Allen brain atlas), suggesting that Purkinje axon terminals may be directly affected by chondroitin sulfate digestion.…”
Section: Discussionmentioning
confidence: 49%
“…We also found that ch'ase induced a decrease in the density of VGLUT1+ terminals in the DLH and adjacent areas of the IntA. The observed differential effects of ch'ase on distinct types of cerebellar synapses might be due to a specific distribution of receptors for CSPGs (69) and/or for Sema3A (19). Purkinje cells show a strong expression of receptors for CSPG-chondroitin sulfates, such as PTPsigma and NgR3 (Allen brain atlas), suggesting that Purkinje axon terminals may be directly affected by chondroitin sulfate digestion.…”
Section: Discussionmentioning
confidence: 49%
“…PNs in the central nervous system are most commonly associated with reduced structural synaptic plasticity (Corvetti and Rossi, 2005;Frischknecht et al, 2009;Karetko-Sysa et al, 2014;Sonntag et al, 2015;see review: Duncan et al, 2019). The role of PNs in structural synaptic plasticity has been further confirmed with many studies demonstrating that the removal of PNs in cortex, via enzymatic digestion, leads to increased plasticity in the visual cortex, learning and memory circuits and fear conditioning (Pizzorusso et al, 2006; see reviews: Wang and Fawcett, 2012;Duncan et al, 2019;Testa et al, 2019). In the current study we demonstrate a significant increase of PNs on both non-GABAergic and GABAergic IC cells.…”
Section: Potential Functional Roles Of Pns In Age-related Hearing Lossmentioning
confidence: 84%
“…Of these functions the inhibition of plasticity has garnered the most attention as the enzymatic disruption of PNs can restore juvenile-like plasticity in the adult cortex (Pizzorusso et al, 2002(Pizzorusso et al, , 2006Gogolla et al, 2009). This apparent role for PNs in the diminished neural plasticity that characterizes the aging brain, along with an increasing aging population, has generated strong interest in the role of PNs in the cortex during neurodegenerative diseases and aging (see reviews Burke and Barnes, 2006;Karetko and Skangiel-Kramska, 2009;Bosiacki et al, 2019;Duncan et al, 2019;Testa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of compounds that digest PNNs significantly reduces Aβ burden as well as increasing synaptic density. This advance introduces the possibility of modulating the PNN, either through PNN digestion or targeting the interaction of various affiliated molecules to the core components of the PNNs, as starting points for an AD therapy (Duncan, Foster, & Kwok, ). Ferroptosis is another potential mechanism that could contribute to neurodegeneration in AD (Nikseresht, Bush, & Ayton, ).…”
Section: Recognition Of a Need For Novel Therapiesmentioning
confidence: 99%